HUBUNGAN KEPERCAYAAN DIRI DENGAN HASIL BELAJAR PEMBUATAN HIASAN BUSANA SISWA KELAS XI DI SEKOLAH MENENGAH KEJURUAN 3 KLATEN - 22, Wuryandari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
The purpose of this study was to determine (1) the level of self-confidence of class XI students, (2) the learning outcomes of making clothes decoration for class XI students, (3) the relationship between self-confidence and the learning outcomes of making clothes ornaments for class XI. Methods of data collection used questionnaires and documentation methods. The data analysis technique used descriptive analysis techniques and hypothesis testing using the Product Moment correlation test which was preceded by the analysis prerequisite test, namely normality and linearity tests. The results showed that (1) the level of self-confidence of class XI students was included in the sufficient category with a percentage obtained of 74.14%, (2) The learning outcomes of making fashion ornaments for class XI students were included in the sufficient category with a percentage obtained of 53.45 %, (3) There is a relationship between self-confidence and the learning outcomes of making clothes decoration for class XI students at SMK Negeri 3 Klaten, with a value of r_count (0.635) > r_table (0.218), and the value of the determinant (R²) of 0.403 which means that the self-confidence variable contributes as much as 40.3% to the learning outcomes of Making Fashion Decorations. keyword: Confidence, Learning Outcomes, Fashion Decoration.